Atonement [compact disc, unabridged] : a novel - McEwan, Ian (Recorded Books, 2007)
In the summer of 1935, 13-year-old Briony Tallis wildly misinterprets the relationship between her sister Cecilia and Robbie Turner, childhood friends home from Cambridge. So when her young cousin is assaulted, Briony gives in to her hyperactive imagination and blames the atrocity on Robbie. It is a terrible decision that alters lives and fills Briony with an everlasting sense of guilt.